1980
DOI: 10.1080/00380768.1980.10431245
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation patterns of microbial numbers in soil applied with compost

Abstract: Plateand direct-counts of bacteria as well as hyphal length were determined in fields applied annually for 10 years with definite amounts of artificial compost made from rice straw. The succession of microbial groups was observed after application of the compost. The direct-count of bacteria increased immediately and reached its highest level just after the compost application in October. The plate-counts of bacteria on conventional media such as albumen and nutrient broth agars fluctuated in a similar manner … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 7 publications
3
25
0
Order By: Relevance
“…The bacterial numbers were largest in Konosu (6.6 x 10 1°-7.6 x 10 10 /g oven dry soil), followed by Aizu (2.2 x IOlD-2.8 x 10 10 jg oven dry soil), and then Shizuoka (1.1 x 10 1°-1.3 x 10 10 jg oven dry soil). The bacterial numbers in paddy soils counted by other authors were reported to be 10 9 orderjg oven dry soil (17,19). The 10 1o order bacteria observed by the authors were about ten times as numerous as the former figures.…”
Section: Bacterial Countssupporting
confidence: 61%
See 1 more Smart Citation
“…The bacterial numbers were largest in Konosu (6.6 x 10 1°-7.6 x 10 10 /g oven dry soil), followed by Aizu (2.2 x IOlD-2.8 x 10 10 jg oven dry soil), and then Shizuoka (1.1 x 10 1°-1.3 x 10 10 jg oven dry soil). The bacterial numbers in paddy soils counted by other authors were reported to be 10 9 orderjg oven dry soil (17,19). The 10 1o order bacteria observed by the authors were about ten times as numerous as the former figures.…”
Section: Bacterial Countssupporting
confidence: 61%
“…NISUIO et al (19) determined the numbers of bacteria stained with acridine orange by direct microscopy. They showed that in Konosu the bacterial number in the organic manure plot (OM) was 5 x 10 9 /g oven dry soil, and that in the inorganic fertilizer one (IF), the number was 3 x 10 9 /g oven dry soil.…”
Section: Bacterial Countsmentioning
confidence: 99%
“…The addition of organic matter enhances the density of microorganisms (Nishio and Kusano 1980) including phosphate-solubilizing microorganisms, which mobilize the non-labile P by secretion of organic acids such as citric acid, gluconic acid or lactic acid (Chen et al 2006). The increased population density of phosphate-solubilizing microorganisms by organic amendments may be partially responsible for an increased level of P uptake by plants.…”
Section: Introductionmentioning
confidence: 99%
“…however, have been made to examine the quantitative relationship between the amount of organic material applied and the soil biomass (Nishio et al 1976;Nishio and Kusano 1980). Recently, since the type of organic material applied to cropland has tended to increase, it has become necessary to evaluate the effect of various types of organic materials on the soil biomass content.…”
mentioning
confidence: 99%